Jawabanmu

2014-04-25T17:15:37+07:00
Lim(x->0) (3x)sin^6x/tan^3(2x) = lim    3xSin^6x
                                               x⇒0  tan³2x
                                            =  lim   3x  Sin³x    Sin³x                                                                                            x⇒0      Tan³2x      x³
                                           =  lim   (3x)(x³)(1)(1)
                                               x⇒0            2  1
                                           =  lim  (3x^4)    terus x nya ganti oleh nol
                                              x⇒0    2
                                           = 0/2)
                                           = 0